Hybridized Fe/Ru-SiMWCNT-ionic liquid nanofluid for CO2 conversion into carbamate using superoxide ion. Issue 4 (August 2021) - Halilu, Ahmed; Hayyan, Maan; Aroua, Mohamed Kheireddine; Yusoff, Rozita; Hizaddin, Hanee F.; Basirun, Wan Jefrey
Abstract: Suppressing the nucleophilic susceptibility of ionic liquids based nanofluid is necessary for energy storage and superoxide ion (O2 − ) utilization. This study reports the development of novel pseudocapacitive Fe/Ru-SiMWCNT nanofluid comprising of Fe3 O4, RuO2, SiO2, and MWCNT hybridized phases. The Fe/Ru-SiMWCNT nanohybrid possessed CO2 and O2 sorption capability, as confirmed from the temperature-programmed desorption experiments. Detailed spectroscopy techniques characterize the Fe/Ru-SiMWCNT nanohybrid component's physicochemical and morphological properties. The novel ionic liquid (IL) based nanofluid index is Fe/Ru-SiMWCNT/1-(2-methoxyethyl)-1-methylpyrrolidinium tris(pentafluoroethyl) trifluorophosphate. Therefore, stable O2 − was generated therein at −0.445 V vs Ag/AgCl and recorded long-term stability for 2 days with 87.31 % efficiency. Moreover, the O2 − mediated CO2 conversion to C2 O6 2− at −0.54 V vs Ag/AgCl with 97.90 % energy efficiency. Also, the normalized exchange current density in the nanofluid was 2.20 mA/cm 2, which is higher than 1.94 mA/cm 2 observed in the IL counterpart. The high normalized exchange current density is due to Fe/Ru-SiMWCNT nanohybrid phase's pseudocapacitance. Accordingly, this pseudocapacitive capability enables converting O2 and CO2 in the nanofluid with lower activation overpotential of −0.305 and −0.460 V vs Ag/AgCl, respectively. In contrast, the conversion of O2 and CO2 in the IL required higher activation overpotential of −0.826 and −1.013 V vs Ag/AgCl, respectively. The electrolysis of O2 /CO2 in the nanofluid containing diethanolamine at −1.564 V vs Ag/AgCl, 60 °C and 1.0 h produced methyl 2-hydroxyethyl (methyl) carbamate as the primary product. The heteronuclear multiple bond correlation spectroscopy analysis finally elucidated the carbamate structure by two strong correlations between the protons and carbons in the vicinity of three and four bonds apart. Therefore, this study highlights the control design of electrochemically stable IL-based nanofluids robust for reactive oxygen species, energy storage and conversion. Graphical Abstract: ga1 Highlights: A new Fe/Ru-SiMWCNT nanohybrid medium was successfully synthesized. Fe/Ru-SiMWCNT afforded first-time electrochemical generation of stable O2 − . The O2 − mediated CO2 conversion into carbamate. The IL-based nanofluid showed a substantial role in the applications of radicals.